Barokah Kyai dan Kebahagiaan Santri Milenial - Aprezo Pardodi Maba; Anugrah Intan Cahyani; Mispani (Kopertais Wilayah XV Lampung, 2021)
Being happy is everyone's hope. There are many ways to get it. However, some people still prefer to devote themselves to the kyai of Islamic boarding school, the reason is to obtain baraka. This paper aims to understand the happiness of servant students in the millennial era and what are factors that influence it. A qualitative phenomenological approach is used to understand how the process is. Three servant students were involved in becoming participants after meet several criteria that have been decided by the author. Semi-structured interviews with participants were used to obtain the data. The data were written down to be an interview transcript. Then the interview transcript was analyzed using the phenomenological method. The writer found that the millennial servant students were happy by dedicating themselves to the kyai, the main motivation of serving them was to obtain baraka. Obedience to the kyai makes a transcendental relationship to God which were manifested by being patient, humble, sincere, and prejudiced. The transcendental relationship has an impact on happiness and peace of heart. The implications and benefits of research will be discussed.